Christmas in U.S. K-12 schools: categorizing and explaining teacher awareness of Christo-normativity. Issue 4 (3rd July 2020) - Puchner, Laurel; Markowitz, Linda
ABSTRACT: To reduce Christo-normativity in United States of America schools, most schools tend to only educate teachers about what religious practices are allowed by law. The question we ask is whether a focus on structural policies, like law, works. We apply Bourdieu's theory of habitus, capital, and field to discuss the findings from 27 interviews we completed with teachers/administrators. We found that participants tended to fit into five categories related to their awareness of whether they promoted Christo-normativity. Those who were relatively aware were either Apologists or Non-celebrators and those who were less aware were Non-apologists, Promoters, or Deniers. We argue that while structural policies to reduce Christo-normativity in public schools may be effective for Apologists and Non-celebrators, such a policy may be ineffective or resisted among Non-apologists, Promoters or Deniers.